Looking for discrete UV absorption features in the early-type eclipsing binaries mu1 Scorpii and AO Cassiopeiae - Arias, María Laura (2005)
A search for discrete absorption components in the ultraviolet spectra of the early-type binaries mu1 Scorpii and AO Cassiopeiae has been undertaken by analyzing material secured with the International Ultraviolet Explorer satellite during an exclusively assigned interval of nearly 50 hr. While the spectra of mu1 Sco definitely do not show the presence of such lines, the spectra of AO Cas do confirm them and permit us to draw some conclusions about where they may be formed.